CompuFax a facsimile tool - Brillo, Ryan Bel C.; Caballero, Hazel B.; Macalinao, Dick O.
Sending and receiving data are made possible by computers and fax machines. Instead of the making communication exclusive from computer to computer and from fax machine to fax machine, this software will allow communication from computer to fax machine and vice versa.